2011
DOI: 10.1309/ajcpoqnbkcdxfwu3
|View full text |Cite
|
Sign up to set email alerts
|

A Well-Designed Online Transfusion Reaction Reporting System Improves the Estimation of Transfusion Reaction Incidence and Quality of Care in Transfusion Practice

Abstract: Recognizing and reporting a transfusion reaction is important in transfusion practice. However, the actual incidence of transfusion reactions is frequently underestimated. We designed an online transfusion reaction reporting system for nurses who take care of transfusion recipients. The common management before and after transfusion and the 18 most common transfusion reactions were itemized as tick boxes. We found the overall documented incidence of transfusion reaction increased dramatically, from 0.21% to 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
1
16
0
2
Order By: Relevance
“…The CDS nursing studies have focused on: adherence to specific guidelines (Campion, Waitman, Lorenzi, May, & Gadd, 2011; Dumont & Bourguignon, 2012; Sward, Orme, Sorenson, Baumann, & Morris, 2008; Welch et al, 2015); single condition nursing diagnostic decision making (Fick, Steis, Mion, & Walls, 2011; Lee et al, 2009; Sawyer et al, 2011; Welch et al, 2015); medication dosing (Campion et al, 2011; Dumont & Bourguignon, 2012; Sward, Orme, Sorenson, Baumann, & Morris, 2008); supporting situational awareness (Dowding et al, 2009; Dumont & Bourguignon, 2012; Sward et al, 2008; Welch et al, 2015); and triage decision making (Dowding et al, 2009; Ernesäter, Holmström, & Engström, 2009; Lee et al, 2009). Findings provide preliminary evidence that nursing CDS can improve accuracy (Lee et al, 2009; Yeh et al, 2011) and efficiency of nursing care (Effken, Loeb, Kang, & Lin, 2008; Sawyer et al, 2011) and patient outcomes (Ruland et al, 2010; Welch et al, 2015). …”
mentioning
confidence: 91%
“…The CDS nursing studies have focused on: adherence to specific guidelines (Campion, Waitman, Lorenzi, May, & Gadd, 2011; Dumont & Bourguignon, 2012; Sward, Orme, Sorenson, Baumann, & Morris, 2008; Welch et al, 2015); single condition nursing diagnostic decision making (Fick, Steis, Mion, & Walls, 2011; Lee et al, 2009; Sawyer et al, 2011; Welch et al, 2015); medication dosing (Campion et al, 2011; Dumont & Bourguignon, 2012; Sward, Orme, Sorenson, Baumann, & Morris, 2008); supporting situational awareness (Dowding et al, 2009; Dumont & Bourguignon, 2012; Sward et al, 2008; Welch et al, 2015); and triage decision making (Dowding et al, 2009; Ernesäter, Holmström, & Engström, 2009; Lee et al, 2009). Findings provide preliminary evidence that nursing CDS can improve accuracy (Lee et al, 2009; Yeh et al, 2011) and efficiency of nursing care (Effken, Loeb, Kang, & Lin, 2008; Sawyer et al, 2011) and patient outcomes (Ruland et al, 2010; Welch et al, 2015). …”
mentioning
confidence: 91%
“…The reported frequency of adverse reactions in the IT‐based reporting system was significantly higher (2.18%) than in the paper‐based reporting system (0.20%). Yeh and colleagues described a similar trend, where the reported frequency of adverse reactions increased from 0.21% to 0.61% after a change in the reporting procedure from a paper‐based reporting system to an IT‐based reporting system. However, Yeh and colleagues did not specifically report the frequencies of reaction after transfusion for each blood component nor report the frequencies in relation to the severity of reaction.…”
Section: Discussionmentioning
confidence: 73%
“…As for transfusion reactions, we observed that they affect lesser than 1% of patients (24) . The most common clinical manifestations include fever, chills, nausea, vomiting, diarrhea, flushing, itching, urticaria, respiratory whistle, dyspnea, headache, hypertension, chest pain and back pain, circulatory collapse, respiratory insufficiency, and shock (25) .…”
Section: Discussionmentioning
confidence: 80%